Bat microfilariae in the cityscape: a transmission tale between bats, mites, and bat flies - Espinal-Palomino, Román; Montes de Oca-Aguilar, Ana Celia; Ibarra-López, Martha Pilar; Vidal-Martínez, Víctor M.; Ibarra-Cerdeña, Carlos N. (International journal for parasitology, 2025)
[Display omitted] •The first known demonstration of the presence of Litomosoides, a bat microfilaria, in bats in an urban landscape.•Bat microfilaria prevalence is higher in tropical forests compared with urban areas in Mexico.•Within urban areas, impervious surfaces harbor bats with higher microfilaria prevalence than the city periphery.•A potential new species of Litomosoides was discovered in bats, mites, and bat-flies. Litomosoides includes filarial nematodes capable of infecting various vertebrate species. While Litomosoides has been extensively studied in rodents, research on its association with bats remains limited. The transmission dynamics of this parasite are complex, involving moving between different invertebrate hosts before reaching the final host. Most investigations concerning microfilariae have concentrated on their morphological characteristics, with scant attention paid to ecological aspects, particularly in human-altered landscapes. This study represents the first known documentation of Litomosoides in bats within an urban environment. It investigates their response to urbanization in their interaction with the synanthropic bat Artibeus jamaicensis and its ectoparasites. The objective was to explore the influence of urban landscapes on Litomosoides prevalence in synanthropic hosts. Blood samples were collected along urban–rural gradients, and parasite presence was confirmed through direct observation in blood smears and PCR. Phylogenetic analysis based on the mitochondrial cytochrome c oxidase subunit 1 gene (COX1), which exhibited robust support values, indicates that the microfilaria found in A. jamaicensis is closely related to Litomosoides chandleri. However, it also suggests the possibility of an unidentified, and therefore potentially new, species within the genus Litomosoides. Additionally, Litomosoides DNA was detected in Periglischrus iheringi (Acari: Spinturnicidae) and in the bat fly Trichobius intermedius collected from the bat. The parasite sequences obtained from these three interacting species exhibited a genetic distance as low as 0.002. The highest prevalences were recorded in forested areas (28.6%) compared with urban areas (21.2%). However, within the urban landscape, prevalence varied from 3.8% to 21.2%, being highest in densely built-up areas. Analysis of the urban landscape suggested that the prevalence of Litomosoides in A. jamaicensis is the result of a multifactorial and synergistic process involving ectoparasite load, host abundance, and the extent of impervious surfaces (NDBI).